Economic sustainability of organic dairy sheep systems in Central Spain - Paula Toro-Mujica; Antón García; Claudio Aguilar; Raúl Vera; José Perea; Elena Angón (Italian Journal of Animal Science, 2015)
Sheep production systems in regions with a Mediterranean climate are important in social, economic and environmental terms. Modeling these systems allows, among others, evaluation of the costs efficiencies which in turn permits assessing the expected effects of changes in production variables. This paper presents a prototype analysis of the economic sustainability of ecological dairy sheep systems of Castilla-La Mancha, Central Spain evaluated through the estimation of costs efficiencies. Costs functions were developed using data from 31 farms. Rate of supplementary feeding, labour use, and flock size were used to measure the cost efficiency. On average, cost efficiency was 61.7±15.5%, with significant differences among typological groups. High efficiency was found in only 29% of the farms. The economic analyses performed suggest that the continued existence of economically unsustainably farms is explained by the available subsidies, lack of amortization of fixed assets leading to progressive decapitalization, and subsistence incomes by family groups (gross family income).